Landscape Design for the South Labuhanbatu District Government Office Based on Eco-Design - Heri Syahputra Pratama Siregar; Akhmad Arifin Hadi (Universitas Bandar Lampung (UBL), 2023)
The Labuhanbatu Selatan city (KLS) is a newly expanded city established in 2008. The city is currently still in the development stage and has overcome the clearing of land for settlements, plantations, and government offices. Besides the infrastructure, the city also needs a public green open space that can balance the ecosystem and human needs. The city government office is an area that can be optimized as a city park. This study aims to create a design concept and design the landscape of the KLS government office. This research was conducted using a descriptive method through a field survey and questionnaires distribution, which was done in four stages: preparation stage, data collection, data processing (concept, analysis, and synthesis), and design. The results show that KLS landscape can be improved by adding trees, shrubs, lawns, retention ponds, plazas, and benches to conserve ecology and human amenity.